Livestock Breeding in the South of Uzbekistan in 1925-1956 (Example of Kashkadarya Region) - Ruziboev Dilshod Azam ugli (Global Scientific Publishing, 2023)
This article reveals the changes in the number of livestock in the Kashkadarya oasis before and after the war, as related problems, livestock used in agricultural work, collective farms, and private farms and changes in their number.
Keywords: Cattle; working horses; mule; collective farm